Edukasi Anak-anak tentang Fenomena Gerhana dan Halo Matahari di Kota Pekanbaru - Utih Amartiwi (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2023)
The decline in Indonesia's PISA scores for student science literacy in 2018 serves as an evaluation of our education system. Education in the 21st century needs to be designed differently from the previous system, as it demands the ability to compete globally and meet the challenges of the 2045 demographic bonus. To address this, the Ministry of Education and Culture (Kemendikbud) has introduced the concept of